Impact of lifestyle on salivary microbiota composition and antibiotic resistance in adult periodontitis patients - Saranya S; Saveetha Priya V; Roja B; Shreejaa C; SenthilKumar N; Chellapandi P (Antonie van Leeuwenhoek, 2026)

Aflatoxin detection and quality assessment in dried red chilli (Capsicum annum L.): A multifaceted approach using physical, microstructural, and machine learning techniques - M. Balasubramaniyan; J. Shavani Durga; V. Chelladurai; T. Senthilkumar; T. Krishnakumar; G. Jeevarathinam (Journal of Stored Products Research, 2026)

Deciphering the potential Zea nicaraguensis for addressing yield plateau in maize - Priya Garkoti; Velmurugan Senthilkumar; Thotla Naresh; Sachin Prakash; T. V. Anirudh; Mayank Tiwari; Kamlesh Kumar; Narendra Kumar Singh (Genetic Resources and Crop Evolution, 2025)

The Impact Assessment of Mechanized Transplanting of Sugarcane Settlings Using Economic Surplus Approach - K. P. Saha; Dushyant Singh; T. Senthilkumar; S. P. Singh; Rajni Jain; Manoj Kumar; V. Bhushanababu (Sugar Tech, 2025)

Recent progress in nanocellulose-based biocomposites for bone tissue engineering and wound healing applications - V. Parthasarathy; P. Senthil Kumar; Annie Aureen Albert; Senthilkumar Krishnasamy; M. Chandrasekar (Carbohydrate Polymers, 2025)

Genotype × Environment Interaction Analysis and Simultaneous Selection Using AMMI, BLUP, GGE Biplot and MTSI Under Drought Condition in Sweet Potato - K. H. Gowda; V. B. S. Chauhan; M. Nedunchezhiyan; C. Pradeepika; K. M. Senthilkumar; V. Chandra; G. Byju; M. R. Sahoo; K. Pati; R. Arutselvan (Journal of Soil Science and Plant Nutrition, 2025)

Short-Term Response of Mandous Severe Cyclone on Coastal Water Quality Along Southwestern Bay of Bengal, India - Subhasis Pradhan; P. Senthilkumar; Umakanta Pradhan; Subrat Naik; Rabindra Kumar Sahoo; Anitha Gera; Uma Sankar Panda; Pravakar Mishra; M. V. Ramana Murthy; P. Vipin Babu (Pure and Applied Geophysics, 2025)

Genome analysis, identification, and expression analysis of nitrogen and potassium responsive genes in cassava - Swathy Sivan; Senthilkumar K. Muthusamy; M. N. Sheela; K. Arya; B. S. Revathi; P. V. Abhilash; R. S. Neethu; A. Pooja; B. S. Prakash Krishnan (Acta Physiologiae Plantarum, 2025)

Assessing potential of teosinte in diversification of maize germplasm for kernel protein - S. Varalakshmi; Narendra Kumar Singh; Navneet Pareek; V. Senthilkumar (Genetic Resources and Crop Evolution, 2025)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Exploring luminescent carbon dots derived from syrup bottle waste and curcumin for potential antimicrobial and bioimaging applications - Natesan Thirumalaivasan; Kuppusamy Kanagaraj; Kamaraj Logesh; Sridhar Chandrasekaran; Sandeep Kumar; Raghunandhakumar Subramanian; Nangan Senthilkumar; Ashok Kumar; V. Jagadeesha Angadi; Abdullah A. Al-Kahtani (Chemosphere, 2024)

Single-Atom catalysts for oxygen reduction reaction and methanol oxidation reaction - Jasvinder Kaur; Vivek Sharma; Dipak Kumar Das; Bidhan Pandit; Mohd Shahzad Samdani; Mohd Shkir; M. Aslam Manthrammel; Senthilkumar Nangan; V. Jagadeesha Angadi; Mohd Ubaidullah (Fuel, 2024)

Engineering of hollow mesoporous Fe-graphitic carbon Nitride@CNTs for superior electrocatalytic oxygen reduction reaction - Anuj Kumar; Ram K. Gupta; Mohd Ubaidullah; Abdullah M. Al-Enizi; Bidhan Pandit; Senthilkumar Nangan; V. Jagadeesha Angadi; Ghulam Yasin (Fuel, 2024)

Assessment of solar thermal monitoring of heat pump by using zeolite, silica gel, and alumina nanofluid - G. Antony Casmir Jayaseelan; A. Surenderpaul; T. Thandial Selvam; A. Anderson; A. Senthilkumar; Avinash Malladi; R. Venkatesh; V. N. Aneesh; R. Saravanan (Clean Technologies and Environmental Policy, 2023)

Molecular detection of porcine parvovirus 1–associated reproductive failure in southern India - S. Parthiban; R. K. V. Sowndhraya; P. Raja; M. Parthiban; A. Ramesh; G. Dhinakar Raj; K. Senthilkumar; D. Balasubramanyam; S. Hemalatha; R. Bharathi; Chintu Ravishankar; S. Thahira Parveen (Tropical Animal Health and Production, 2022)

Investigation of Geochemical Characterization and Groundwater Quality with Special Emphasis on Health Risk Assessment in Alluvial Aquifers, South Africa - P. P. Mthembu; V. Elumalai; M Senthilkumar; J. Wu (International Journal of Environmental Science and Technology, 2021)

Sustenance of Indian Moored Buoy Network During COVID-19 Pandemic – A Saga of Perseverance - R. Venkatesan; K. Jossia Joseph; C. Anoopa Prasad; M. Kalyani; M. Arul Muthiah; S. Ramasundaram; P. Murugesh; K. Thirumurugan; R. Sundar; B. Kesavakumar; G. Vengatesan; K. Ramesh; et al. (Frontiers in Marine Science, 2021)
The moored buoy network in the Indian Ocean revolutionized the observational programs with systematic time-series measurement of in situ data sets from remote marine locations. The real-time meteorological and oceanographic data sets significantly improved the weather forecast and warning services particularly during extreme events since its inception in 1997. The sustenance of the network requires persistent efforts to overcome the multitude of challenges such as vandalism, biofouling, rough weather, corrosion, ship time availability, and telemetry issues, among others. Besides these, the COVID-19 pandemic constrained the normal functioning of activities, mainly by delaying the maintenance of the network that resulted in losing a few expensive buoy system components and precious data sets. However, the improvements in the buoy system, in-house developed data acquisition system, and efforts in ensuring the quality of measurements together with “best practice methods” enabled 73% of the buoy network to be functional even when the cruises were reduced to 33% during the COVID-19 lockdown in 2020. The moored buoys equipped with an Indian buoy data acquisition system triggered high-frequency transmission during the Super cyclone Amphan in May 2020, which greatly helped the cyclone early warning services during the COVID-19 pandemic. The COVID-19 lockdown points toward the reliability and enhanced utility of moored buoy observations particularly when other modes of measurements are limited and necessitates more such platforms to better predict the weather systems. The present study analyzed the enhancement of the buoy program and improvisation of the buoy system that extended the life beyond the stipulated duration and enabled the high-frequency data transmission during cyclones amid the COVID-19 lockdown. The recommendations to better manage the remote platforms specifically in the event of a pandemic based on the operational experience of more than two decades were also presented.

Genetic control of adventitious rooting traits in bi-parental pedigree of Eucalyptus tereticornis × E. camaldulensis - Varadarajan Muthulakshmi; C. V. Vijayam; Vijaya Kumar Waman Bachpai; Veerasamy Sivakumar; Eswaran Muthulakshmi; Senthilkumar Shanmugavel; Abdul Bari Muneera Parveen; Ramasamy Yasodha; D. Rajasugunasekar; Binai Nagarajan; Annamalai Mayavel; Modhumita Ghosh Dasgupta (New Forests, 2021)

Impact of landuse on the groundwater quality along coastal aquifer of Thiruvallur district, South India - S. Senthilkumar; B. Gowtham; M. Sundararajan; S. Chidambaram; J. Francis Lawrence; M. V. Prasanna (Sustainable Water Resources Management, 2018)

Stability of micro-tidal inlets along coastlines dominated by littoral drift - R. Senthilkumar; K. Murali; V. Sundar (Journal of Coastal Conservation, 2017)

Geotechnical characterization and analysis of rainfall—induced 2009 landslide at Marappalam area of Nilgiris district, Tamil Nadu state, India - V. Senthilkumar; S.S. Chandrasekaran; V.B. Maji (Landslides, 2017)

Preliminary Analysis of Polycyclic Aromatic Hydrocarbons in Air Particles (PM10) in Amritsar, India: Sources, Apportionment, and Possible Risk Implications to Humans - Simerpreet Kaur; Kurunthachalam Senthilkumar; V. K. Verma; Bhupander Kumar; Sanjay Kumar; Jatinder Kaur Katnoria; C. S. Sharma (Archives of Environmental Contamination and Toxicology, 2013)

A Rare Cause of Late-Onset Cerebellar Ataxia: Erdheim–Chester Disease - Senthilkumar V. Shanmugam; Madhan Kolappan; Mamta Garg; Winston J. Rennie; Peter Furness; Yusuf A. Rajabally (The Cerebellum, 2013)

Computational analysis of deleterious missense mutations in aspartoacylase that cause Canavan’s disease - K. Sreevishnupriya; P. Chandrasekaran; A. Senthilkumar; R. Sethumadhavan; V. Shanthi; P. Daisy; J. Nisha; K. Ramanathan; R. Rajasekaran (Science China Life Sciences, 2012)

Evaluation of the cocktail recombinant antigens, LipL32 and LipL41 for serodiagnosis of canine leptospirosis - M. Subathra; T. M. A. Senthilkumar; P. Ramadass; V. Ramaswamy (World Journal of Microbiology and Biotechnology, 2011)

Influence of hydraulic retention time in a two-phase upflow anaerobic sludge blanket reactor treating textile dyeing effluent using sago effluent as the co-substrate - M. SenthilKumar; G. Gnanapragasam; V. Arutchelvan; S. Nagarajan (Environmental Science and Pollution Research, 2011)

Recycle in upflow anaerobic sludge blanket reactor on treatment of real textile dye effluent - G. Gnanapragasam; M. Senthilkumar; V. Arutchelvan; P. Sivarajan; S. Nagarajan (World Journal of Microbiology and Biotechnology, 2010)

Serodiagnosis of bovine leptospirosis by IgG-Enzyme-Linked Immunosorbent Assay and Latex Agglutination Test - T. M. A. Senthilkumar; M. Subathra; P. Ramadass; V. Ramaswamy (Tropical Animal Health and Production, 2010)

Effects of selected heavy metals (Pb, Cu, Ni, and Cd) in the aquatic medium on the restoration potential and accumulation in the stem cuttings of the terrestrial plant, Talinum triangulare Linn - K. Rajkumar; S. Sivakumar; P. Senthilkumar; D. Prabha; C. V. Subbhuraam; Y. C. Song (Ecotoxicology, 2009)

Characterization of multiple promoters and transcript stability in the sacB–sacC gene cluster in Zymomonas mobilis - V. Senthilkumar; J. Rajendhran; S. J. W. Busby; P. Gunasekaran (Archives of Microbiology, 2009)

Biocontrol Potential of Soybean Bacterial Endophytes Against Charcoal Rot Fungus, Rhizoctonia bataticola - M. Senthilkumar; K. Swarnalakshmi; V. Govindasamy; Young Keun Lee; K. Annapurna (Current Microbiology, 2009)

Detection and Characterization of ACC Deaminase in Plant Growth Promoting Rhizobacteria - V. Govindasamy; M. Senthilkumar; V. Mageshwaran; K. Annapurna (Journal of Plant Biochemistry and Biotechnology, 2009)

Collection of plant genetic resources from Andaman and Nicobar Islands - Z. Abraham; R. Senthilkumar; K. Joseph John; T. V. R. S. Sharma; N. V. Nair; M. Unnikrishnan; P. M. Kumaran; Johnson K. George; S. Uma; M. Latha; S. S. Malik; S. K. Mishra; et al. (Genetic Resources and Crop Evolution, 2008)

Purification and Partial Characterization of Antifungal Peptides from Soybean Endophyte-Paenibacillus sp strain HKA-15 - M. Senthilkumar; V. Govindasamy; P. Dureja; K. Annapurna (Journal of Plant Biochemistry and Biotechnology, 2007)

Role of Antibiosis in Suppression of Charcoal Rot Disease by Soybean Endophyte Paenibacillus sp. HKA-15 - M. Senthilkumar; V. Govindasamy; K. Annapurna (Current Microbiology, 2007)

Effects of Copper Sulfate and Copper Nitrate in Aquatic Medium on the Restoration Potential and Accumulation of Copper in Stem Cuttings of the Terrestrial Medicinal Plant, Portulaca Oleracea Linn - S. Mohanapriya; P. Senthilkumar; S. Sivakumar; M. Dineshkumar; C. V. Subbhuraam (Environmental Monitoring and Assessment, 2006)

Plant Growth–Promoting Methylobacterium Induces Defense Responses in Groundnut (Arachis hypogaea L.) Compared with Rot Pathogens - M. Madhaiyan; B. V. Suresh Reddy; R. Anandham; M. Senthilkumar; S. Poonguzhali; S. P. Sundaram; Tongmin Sa (Current Microbiology, 2006)

Copper Availability and Accumulation by Portulaca Oleracea Linn. Stem Cutting - R. Deepa; P. Senthilkumar; S. Sivakumar; P. Duraisamy; C. V. Subbhuraam (Environmental Monitoring and Assessment, 2006)

Delineation of potential zones for artificial recharge using gis - V Jothiprakash; G Marimuthu; R Muralidharan; N Senthilkumar (Journal of the Indian Society of Remote Sensing, 2003)

Mulberry-Silkworm Food Chain – A Templet to Assess Heavy Metal Mobility in Terrestrial Ecosystems - SPM. Prince; P. Senthilkumar; V. Subburam (Environmental Monitoring and Assessment, 2001)

Isolation, PCR based identification, and sensitivity pattern of environmental mycobacteria from leprosy and tuberculosis patients - D. Saravanakumar; N. Elangeswaran; S. Senthilkumar; G. Vanaja; S. Kamakshiammal; C. Chandrasekar; C. N. Deivanayagam; Manjula Sritharan; V. Sritharan (Indian Journal of Clinical Biochemistry, 2000)